IMMUNOSTIMULATORY EFFECTS OF ULVAN ON TRYPSIN-MEDIATED PROTEIN DIGESTION IN THE GUT OF PACIFIC WHITELEG SHRIMP (Litopenaeus vannamei) - Azhar, Nuril; Yudiati, Ervia; Ambariyanto, Ambariyanto; Alghazeer, Rabia; Trianto, Agus (Politeknik Kelautan dan Perikanan Jembrana, 2024)
Litopenaeus vannamei has emerged in the aquaculture industry. Production consistency, nutrition, and disease management play critical roles, particularly the digestive enzymes such as trypsin. This study assesses Ulvan, an immunostimulant from Ulva lactuca, on shrimp trypsin activity. Trypsin has been found to significantly enhance the activity of hemocyanin phenoloxidase, a crucial component of humoral immunity. This study aims to evaluate the potency of ulvan related to trypsin as an immunostimulant agent, extracted from Ulva sp. Ulvan, extracted using various methods (P-HWE, O-HWE, P-A-HWE, and O-A-HWE), was evaluated using different doses of (0 g kg-1 (Control), 0.75 g kg-1 (ULV-0.75), 1.50 g kg-1 (ULV-1.50), and 3.00 g kg-1 (ULV-3.00) of feed). The O-A-HWE exhibited the fastest and highest increase in trypsin activity on day 4, surpassing the control on days 2, 3, 7, and 8. The P-HWE, O-HWE, and P-A-HWE also showed significant changes in trypsin activity compared to the control on specific days. Meanwhile, trypsin activity in Ulvan-fed shrimp did not significantly differ from the control on days 0 and 1. The differences emerged on day 2 and 3, notably between ULV-1.50 g kg−1 and ULV-0.75 g kg−1. The ULV-3.00 g kg−1 showed no significant difference from ULV-1.50 g kg−1. O-A-HWE demonstrated significant differences in trypsin activity compared to other Ulvan extracts, suggesting its potential to enhance shrimp health.Litopenaeus vannamei memiliki peran yang besar dalam industri akuakultur. Konsistensi dalam produksi, nutrisi, dan pengelolaan terhadap penyakit merupakan bagian yang sangat penting, terutama enzim pencernaan, di antaranya tripsin. Tripsin berfungsi untuk meningkatkan fenoloksidase hemosianin, yang peranannya penting untuk kekebalan. Studi ini mengevaluasi Ulvan, yaitu bahan yang bersifat imunostimulan dari Ulva sp., terhadap aktivitas tripsin udang. Ulvan, diekstraksi menggunakan berbagai metode (P-HWE, O-HWE, P-A-HWE, dan O-A-HWE), dievaluasi menggunakan perlakuan dosis yang berbeda (0 g kg-1 (Kontrol), 0,75 g kg-1 (ULV-0,75), 1,50 g kg-1 (ULV-1,50), dan 3,00 g kg-1 (ULV-3,00) pada pemeliharaan udang vaname selama 10 hari. O-A-HWE menunjukkan peningkatan aktivitas tripsin tercepat dan tertinggi pada hari ke-4, melebihi kontrol pada hari ke-2, 3, 7, dan 8. P-HWE, O-HWE, dan P-A-HWE juga menunjukkan perubahan signifikan dalam aktivitas tripsin dibandingkan dengan kontrol pada hari-hari tertentu. Sementara aktivitas tripsin dalam udang yang diberi Ulvan tidak berbeda secara signifikan dari kontrol pada hari ke-0 dan 1, perbedaan mulai terlihat pada hari ke-2 dan 3, terutama antara ULV-1,50 g kg−1 dan ULV-0,75 g kg−1. ULV-3,00 g kg−1 tidak menunjukkan perbedaan yang signifikan dari ULV-1,50 g kg−1. O-A-HWE menunjukkan perbedaan signifikan dalam aktivitas tripsin dibandingkan dengan ekstrak Ulvan lainnya, sehingga berpotensi dalam meningkatkan kesehatan udang.